The Effectiveness of Using Quora Website in Improving Students’ Descriptive Text Writing - Devi Rindiani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aimed to prove whether or not the use of Quora Website was effective in increasing students’ ability in writing descriptive texts. The sample of this study was 10th graders of SMK N 1 Dendang, registered in the academic year of 2022/2023. This research used quantitative method with experimental approach. In collecting the data, both pre-test and post-test were used as the instruments. The results of data analysis showed that the students made progress after they were taught by using Quora website, in which the average score of their post-test, i.e., 79.75 was higher than the one in the pre-test, i.e., 60.63. there was an increase in students' scores from the pre-test and post-test. This finding confirmed that Quora Website was an effective media in the improvement of students’ skills of writing descriptive text.